2015
DOI: 10.1016/j.jmatprotec.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural modification of Ti–6Al–4V by using an in-situ printed heat sink in Electron Beam Melting® (EBM)

Abstract: Please cite this article as: Jamshidinia, M., Atabaki, M.M., Zahiri, M., Kelly, S., Sadek, A., Kovacevic, R.,Microstructural Modification of Ti-6Al-4V by Using an In-Situ Printed Heat Sink in Electron Abstract Unidirectional heat transfer during additive manufacturing (AM) processes results in anisotropy of microstructure and mechanical properties in fabricated components. In the present study, the influence of in-situ printed heat sinks on the microstructure of Ti-6Al-4V was investigated. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 18 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…In this study, α lath thickness was considered as the relevant microstructural characteristic dimension, following a previous work where Hall-Petch equation was proposed for lamellar structured steels [43]. A Hall-Petch type equation was previously suggested for hardness and yield strength of EBM Ti-6Al-4V by Jamshidinia et al [44]. The empirical relation between α lath thickness and hardness values obtained in this study, as well as values shown by other authors [12], Figure 17, was modeled with the following equation:…”
Section: Effects Of Aging Time and Temperaturementioning
confidence: 99%
“…In this study, α lath thickness was considered as the relevant microstructural characteristic dimension, following a previous work where Hall-Petch equation was proposed for lamellar structured steels [43]. A Hall-Petch type equation was previously suggested for hardness and yield strength of EBM Ti-6Al-4V by Jamshidinia et al [44]. The empirical relation between α lath thickness and hardness values obtained in this study, as well as values shown by other authors [12], Figure 17, was modeled with the following equation:…”
Section: Effects Of Aging Time and Temperaturementioning
confidence: 99%
“…Vickers micro-hardness as a function of alpha lath width for Ti-6Al-4V fabricated by AM from [54,152,174,175,176,177,178,179]. Error bars, where available, represent the standard deviation in measurements.…”
Section: Figurementioning
confidence: 99%
“…Other ways to distinguish these technologies are to group them by the physical state of raw materials (i.e., liquid, solid, or powder form) and by the methods that are used to fuse the raw materials together (e.g., thermal, ultraviolet (UV) light, laser, or electron beam) . A number of mature AM technologies have been successfully commercialized such as fused deposition modeling (FDM), direct ink writing (DIW), selective laser sintering, stereolithography (SLA), powder bed inkjet 3D printing (inkjet 3D), two‐photon polymerization, laminated object manufacturing, and their variants such as multijet printing (MJP) and selective laser melting (Figure ). However, how well can these AM processes be used in fabricating biomimetic materials and structures and what is the current status of AM technology development to address the fabrication challenges of biomimetic materials and structures?…”
Section: Introductionmentioning
confidence: 99%